New records of Gyraulus rossmaessleri (Gastropoda: Planorbidae) in the Czech Republic - Luboš Beran (Malacologica Bohemoslovaca, 2005)
Populations of the freshwater snail Gyraulus rossmaessleri (Auerswald, 1852) (Gastropoda, Planorbidae) were found at 4 sites in the Meandry Smědé Nature Reserve (Northern Bohemia, Czech Republic). In Bohemia this species has not been found for last 25 years and the nearest localities with its known occurrence in the past are situated about 100 km to the south-west.